"Draw yourself out of it": Miriam Katin's graphic metamorphosis of trauma. Issue 1 (2nd January 2018) - Oostdijk, Diederik
ABSTRACT: Miriam Katin's two graphic memoirs We Are on Our Own [(2006). Montreal: Drawn & Quarterly] and Letting It Go [(2013). Montreal: Drawn & Quarterly] both reflect on how the trauma of the Holocaust can be transformed through and in art. In the former Katin details how she and her mother narrowly escape the Nazi occupation of Hungary by fleeing to the countryside when she was a toddler, while the latter shows how Katin, who has since emigrated to the United States, is still struggling with anxieties decades after, which are the result of the Holocaust. Using insights from both memory studies and Bessel Van Der Kolk's experimental psychological theories that trauma is an embodied experience and that it can be partly released through physical and creative practices, this essay argues that Katin finds solace through the multimodal activity of drawing and writing herself out of the negative aftereffects that the Holocaust have on her.